The first Singaporean on Mars - Goh, Nasya Ephrath Wei Ying (Nanyang Technological University, 2021)
Set in a dystopian future where Earth has reached the point of no return on climate change, and where colonising another planet is the greatest hope for humanity’s survival, a speculative and fiction-based exhibition is held to celebrate the return of Singaporean astronaut-cum-botanist Nasya Goh from her successful mission to Mars.